2016
DOI: 10.1016/j.nicl.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the anterior forebrain mesocircuit and the default mode network in the structural bases of disorders of consciousness

Abstract: The specific neural bases of disorders of consciousness (DOC) are still not well understood. Some studies have suggested that functional and structural impairments in the default mode network may play a role in explaining these disorders. In contrast, others have proposed that dysfunctions in the anterior forebrain mesocircuit involving striatum, globus pallidus, and thalamus may be the main underlying mechanism. Here, we provide the first report of structural integrity of fiber tracts connecting the nodes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 79 publications
(128 reference statements)
8
65
0
Order By: Relevance
“…4), in line with previous reports [Fern andez-Espejo et al, 2011G omez et al, 2012]. Our results support recent findings of diminished structural integrity of corticocortical and subcorticocortical DMN connections, which correlated with clinical severity in a group of eight patients [Lant et al, 2015].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…4), in line with previous reports [Fern andez-Espejo et al, 2011G omez et al, 2012]. Our results support recent findings of diminished structural integrity of corticocortical and subcorticocortical DMN connections, which correlated with clinical severity in a group of eight patients [Lant et al, 2015].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, in contrast to DOC patients, EMCS patients show a significantly stronger function-structure interaction between the function of the thalamus and the structural integrity of the thalamoinferiorparietal tract. On the uni-modal level our results match previous research in post-comatose patients finding that structural cortico-thalamic connections are diminished [Lant et al, 2015] and thalamic metabolism is lowered [Fridman et al, 2014]. These findings can be explained by the mesocircuit theory, which proposes that large-scale dysfunction is due to a global decrease of excitatory neurotransmission which in turn alters cerebral activity.…”
Section: Discussionsupporting
confidence: 89%
“…Several factors, in addition to the extent of structural lesions, may affect the ability of the residual brain to engage in complex interactions. One possibility to be investigated is whether the integrity of some specific structures, such as the precuneus,20, 37 the thalamus,5, 38 and the claustrum,39, 40 or a critical level of overall anatomical connectivity41 may be key in sustaining such interactions. Another non–mutually exclusive possibility is that the complexity of residual thalamocortical networks may be reduced by functional imbalances leading to an excessive degree of neuronal bistability 42.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we observed that the higher the CRS-R score, the shorter the P 1 latency and the P 2 -P 3 interval. Indeed, CRS-R measures the ability of DOC individuals to receive information and process them in a purposeful way, which lies on the integrity of large-scale cortical-thalamocortical networks (Lant et al 2015). On the other hand, the preservation of peak distribution and inter-peak latencies may reflect the degree of sparing of functional intra-M1 and premotor-M1 connectivity, as suggested by some studies (Davare et al 2010;Lemon, 2012;Shimazu et al 2004), and regardless of the corticospinal tract deterioration (since all the peak and inter-peak latencies were increased by reason of the P 0 delay).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these DOC patients may be misdiagnosed when using the Coma Recovery Scale-Revised (CRS-R). The latter represents a reliable tool to identify the awareness level that specifically correlates with the wide connectivity breakdown (Giacino et al 2004;Kalmar and Giacino, 2005;Gerrard et al 2014;Lant et al 2015). We hypothesized that motor unresponsiveness in some DOC patients might be due to an intra-M1 rather than a premotor-M1 dysfunction.…”
Section: Introductionmentioning
confidence: 96%